Quantitative Analysis Of Elementary School Students' Curiosity and Web-Based Assessment Responses - Asrial Asrial; Syahrial Syahrial; Husni Sabil; Dwi Agus Kurniawan; Rahmat Perdana; Ahmad Mansur Nawahdani; Bob Widodi; Rahmi Rahmi; Pascasie Nyirahabimana (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
The use of web-based assessment at the elementary school level is a novelty in this research. The purpose of this research is to find out the comparison of the character of curiosity and the comparison of student responses to the use of web-based assessment. In addition, it is also to determine the effect of the character of curiosity on student responses in using web-based assessments. This research is quantitative research with associative and comparative research types. The sample used in this study were high school elementary school students at 64 Muara Bulian elementary school and 80 Muara Bulian elementary school. The sam-pling technique in this study was random sampling. The data analysis technique in this study is a quantita-tive analysis technique using data processing assistance. The results of the t test with sig. (2-tailed) less than 0.05, it can be seen that there are differences in the character of students' curiosity and there are differences in student responses to the use of web-based assessments. The results of the regression test with a signifi-cance value of 0.009 which means less than 0.05 so that the character of curiosity influences student re-sponses in using web-based assessments. The significant influence here means that students who have a good character of curiosity will also respond well to the use of web-based assessment.